The elderly as underconsulters: a critical reappraisal - Ford, Graeme (1985)
This paper reconsiders the evidence for underconsultation among the elderly. Earlier evidence from studies of unreported illness is reassessed and new data are presented for the ratio of self-reported illness to number of consultations. It is concluded that underconsultation among the elderly is exaggerated and that there are implications for screening and case-finding. It is suggested that attention should be directed towards a combination of self-referral and multi-tiered screening for low contact and high risk groups.